Os desafios da formação continuada de professores visando à inclusão de alunos com necessidades especiais - Freitas, Maria Isabel Castreghini de [UNESP]; Ventorini, Silvia Elena [UNESP]; Rios, Carla [UNESP]; Araújo, Thais Helena Buzzato de [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
Special Education underwent several changes in the XX century through socialmovements that claimed for equality for all citizens as well as for thesuppression of all sorts of discrimination. This paper has the objective ofrevealing the experience obtained by a team of researchers in a course ofextended formation, presenting the Extended Course for Teachers of PublicSchools in the Municipality of Araras-SP, through the Center of ExtendedMathematics, Scientific and Environmental Education (CECEMCA) of theUniversidade Estadual Paulista -Unesp. The CECEMCA adopted the strategyof centralizing its courses in the Environmental Education and studies related toenvironmental aspects as well as the didactic material related to the courses.Such courses can be with presence, semi-presence or at distance. This paperintends to disseminate the techniques developed in the preparation andapplication of didactic material, specially tactile models in interdisciplinaryactivities aimed at the inclusion of students with special needs, emphasizing theeducation of blind or visually impaired students through a reflexive actiondirecting the practices to Action-Reflection-Action. The presence requiredactivities were composed of theoretical explanations approaching cartographic,geographic and environmental concepts, practical activities in which theparticipants built their didactic sets (tactile models) and reading of accounts anddiscussions about the teaching experiences in projects with the students of theschool. The activities at distance were composed of two parts: extra-classactivities including the development of a project with the students to create athematic tactile model prioritizing the multidisciplinary approach and technicaland practical visits with cartographic material. The experience of the extendedteachers' formation course achieved its objectives when made it possible theinvolvement of teachers of different areas of knowledge. The thematic projectswere developed with their students having as a main theme the cartographyand the inclusion of special needs students.

O presente artigo tem por objetivo divulgar a experiência obtida pelo grupo de pesquisadores em um curso de formação continuada, apresentado no formato de Curso de Extensão para Professores da Rede Pública de Ensino do Município de Araras-SP,através do Centro de Educação Continuada em Educação Matemática, Científica e Ambiental (CECEMCA) da Universidade Estadual Paulista - Unesp. O CECEMCA adotou como estratégia centralizar na Educação Ambiental e nos estudos voltados para os aspectos ambientais a geração de seus cursos, que podem ser presenciais, semi-presenciais e à distância, bem como do material didático a eles relacionados. Este trabalho pretendeu disseminar as técnicas desenvolvidas na construção e aplicação de material didático, em especial maquetes táteis, em atividades interdisciplinares voltadas para a inclusão de alunos com necessidades especiais, com ênfase a educação de alunos cegos e de baixa visão através de uma ação reflexiva, norteando as práticas docentes na Ação-Reflexão-Ação. As atividades presenciais eram compostas por exposições teóricas abordando conceitos cartográficos, geográficos e ambientais; atividades práticas nas quais os participantes construíram conjuntos didáticos (maquetes) e momentos de leitura de relatos e discussões sobre as experiências dos professores nos projetos realizados com os alunos na escola. As atividades a distância eram compostas por duas etapas denominadas atividades extra-classe que incluíram o desenvolvimento de um projeto englobando a construção de uma maquete temática com seus alunos, prioritariamente com abordagem interdisciplinar, bem como visita técnica e prática com material cartográfico. A experiência docurso de formação continuada de professores atingiu seu objetivo ao possibilitar o envolvimento de docentes, atuantes em diferentes áreas do conhecimento. Os projetos temáticos foram desenvolvidos com seus alunos, tendo como tema a cartografia e a inclusão de alunos com necessidades especiais.
Challenges in the extended formation of teachers aiming at the inclusion of special-needs students
Keywords: Course of extended formation; Special education; Cartography; Exatas; Educação; Formação continuada; Educação especial; Cartografia